2001
DOI: 10.1037/0021-9010.86.3.418
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice evaluations, job control, and occupational strain.

Abstract: To explore how organizational justice evaluations affect the occupational stress process, the authors formulated and tested the following 2 hypotheses: (a) The effect of job control on strain is mediated by justice evaluations, and (b) justice evaluations moderate the effect of job control on occupational strain. The results of structural equation modeling, based on data collected from 688 employees, suggest that job control affects strain through justice evaluations. Thus, the results of this study supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
180
4
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 219 publications
(211 citation statements)
references
References 64 publications
21
180
4
4
Order By: Relevance
“…This refers to the extent to which employees are treated justly in their workplace and consists of two components: justice concerning decision-making procedures and interpersonal treatment 25) . Previous studies have shown that lower levels of justice are associated with lower well-being, higher self-reported morbidity, higher medically certified absences, increased mental health problems, and a greater likelihood of maladaptive coping [25][26][27][28] . Hence, the introduction of a health program that improves active coping may be useful for improving the levels of perceived justice.…”
Section: Discussionmentioning
confidence: 99%
“…This refers to the extent to which employees are treated justly in their workplace and consists of two components: justice concerning decision-making procedures and interpersonal treatment 25) . Previous studies have shown that lower levels of justice are associated with lower well-being, higher self-reported morbidity, higher medically certified absences, increased mental health problems, and a greater likelihood of maladaptive coping [25][26][27][28] . Hence, the introduction of a health program that improves active coping may be useful for improving the levels of perceived justice.…”
Section: Discussionmentioning
confidence: 99%
“…The ERI model shares elements with the distributive justice model, another work motivation theory (10), and taps features of postmodern flexible worklife, such as temporary employment and job insecurity (61). The most recent developments in work motivation theories involve procedural and relational justice at work (11,13), which has been shown to be an important moderator of employee responses (62)(63)(64)(65). A further parallel between work motivation theories and stress models is the application of the organizational injustice concept in studies of stress as an etiological factor for CHD.…”
Section: Directions Of Future Researchmentioning
confidence: 99%
“…These components of justice have been used as a theoretical framework in a wide range of contexts (e.g. Elovainio, Kivima¨ki, & Helkama, 2001;Folger & Konovsky, 1989;McFarlin & Sweeney, 1992;Moorman, 1991;van den Bos, Vermunt, & Wilke, 1997).…”
Section: Introductionmentioning
confidence: 99%